(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
BOHECO DESIRE is an Ayurvedic proprietary medicine formulated in capsule form, recommended for enhancing sexual health, libido, stamina, and energy. Objectives: This study aims to explore the molecular binding interactions of the major phytocompounds present in BOHECO DESIRE with a target protein and also to understand binding affinity and bioavailability, using advanced computational tools. Methodology: Molecular docking studies were performed using ChemDraw 20.1.1. Glide extra precision (XP) scoring tools were employed to calculate the docking scores. The binding energy of the receptor-phytoconstituent complexes was calculated using the Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) method. Additionally, the QikProp module from Schrödinger was used to predict the ADME (Absorption, Distribution, Metabolism, Excretion) and physicochemical properties of the phytoconstituents. Results: Docking scores for L-DOPA, Cannabidiol, and Delta-9 Tetrahydrocannabinol suggest strong binding affinity with the target protein 1XOJ, with scores ranging from -9.4 to -4.1 kcal/mol. The van der Waals energy (Glide evdw) between -42.5 and -24.11 kcal/mol indicates favorable ligand-protein interactions. Glide energy, which includes van der Waals, electrostatic, and solvation energies, ranged from -45.07 to -26.53 kcal/mol, reinforcing the potential for stable complexes. Binding free energy values (-76.6 to -35.73 kcal/mol) suggest energetically favorable interactions. ADME predictions showed high oral absorption for Withanolide A, Delta-9 THC, and Cannabidiol, with the highest Caco-2 permeability for Delta-9 THC. Conclusion: The phytoconstituents demonstrated a strong binding affinity with 1XOJ with favorable ADME profiles. This indicates that BOHECO DESIRE’s phytocompounds may have beneficial effects in sexual health.